DEVELOPMENT OF LASER GAIN MEDIUM BASED ON GLASS BORATE DOPED NEODYMIUM ION (Nd3+) - YULIANTINI (NIM : 20215049), LIA
Laser technology has widely used in many fields such as industry, medical, and communication field. In the medical field, the laser is used for the operation and killing of the cancer cell. Meanwhile, in the industry and communication field, the laser is used for cutting steel and data transmission. In this research, we have been developed the glass gain medium doped rare earth ions due to the luminescence in the visible and infrared region. The glass modifier that is used is borate oxide glass due to its high mechanical, chemical and thermal stability. The glass medium composition is 10ZnO:10Al2O3:20BaO: (60-x)B2O3:xNd3+ where x = 0,5; 1,0; 1,5 and 2,0 mol%. The raw material is a powder that has purity of 99.99 % from Sigma-Aldrich. The glass medium was prepared by the melt-quenching method. The sample is melting at 11000C for 3h and annealing at 5000C for 3h. Subsequently, the glass medium was cut and polished in 0,35 x 1 x 1,5 cm3. The characterization consists of physical, optical, and radiative properties. The radiative properties were measured by Judd-Ofelt theory that resulted in several variables. The variables are calculated and experiment oscillator strength (fexp, fcal), JO parameter (Ωλ=2,4,6), stimulated emission cross section (σemi), radiative transition probability (AR), calculated and experiment branching ratio(βcal, βexp). From the resulted data, the prepared glass medium is the potential candidate for a laser gain medium at 1067 nm that is operated by 581 nm wavelength.